Cost-effectiveness of internet-delivered cognitive–behavioural therapy for adolescents with irritable bowel syndrome. Issue 1 (24th January 2019) - Sampaio, Filipa; Bonnert, Marianne; Olén, Ola; Hedman, Erik; Lalouni, Maria; Lenhard, Fabian; Ljótsson, Brjánn; Ssegonja, Richard; Serlachius, Eva; Feldman, Inna
Abstract : Objective: To assess whether exposure-based internet-delivered cognitive–behavioural therapy (internet-CBT) is a cost-effective treatment for adolescents with irritable bowel syndrome (IBS) compared with a waitlist control, from a societal perspective, based on data from a randomised trial. Design: Within-trial cost-effectiveness analysis. Setting: Participants were recruited from the whole of Sweden via primary, secondary and tertiary care clinics reached through news media and advertising. Participants: Adolescents (aged 13–17) with a diagnosis of IBS. Interventions: Participants were randomised to either an exposure-based internet-CBT, including 10 weekly modules for adolescents and five modules for parents, or a waitlist. Outcome measures: The main health outcome was the quality-adjusted life-year (QALY) estimated by mapping Pediatric Quality-of-Life Inventory (PedsQL) scores onto EQ-5D-3L utilities. The secondary outcome was the point improvement on the PedsQL scale. Data on health outcomes and resource use were collected at baseline and 10 weeks post-treatment. Resource use was measured using the Trimbos and Institute of Medical Technology Assessment Cost Questionnaire for Psychiatry (TIC-P) . Incremental cost-effectiveness ratios (ICER) were calculated as the difference in average costs by the difference in average outcomes between groups. Results: The base-case results showed that internet-CBT costs were on average US170.24 (95% CI 63.14 to 315.04) more per participant than the waitlist. Adolescents in the internet-CBT group showed small QALY gains (0.0031; 95% CI 0.0003 to 0.0061), and an average improvement of 5.647 points (95% CI 1.82 to 9.46) on the PedsQL compared with the waitlist. Internet-CBT yielded an ICER of 54 916/QALY gained and a probability of cost-effectiveness of 74% given the Swedish willingness-to-pay threshold. The ICER for the outcome PedsQL was US85.29/point improvement. Conclusions: Offering internet-CBT to adolescents with IBS improves health-related quality of life and generates small QALY gains at a higher cost than a waitlist control. Internet-CBT is thus likely to be cost-effective given the strong efficacy evidence, small QALY gains and low cost. Trial registration number: NCT02306369 ; Results.